Redes sociales y su incidencia en el proceso de enseñanza-aprendizaje en estudiantes del 8vo semestre paralelo “A” en la Universidad Técnica de Babahoyo Extensión Quevedo - Limones Morales, Johanna Stefania (2022)
The purpose of this study was to investigate the potential impact of social networks (SR) in higher education, used as a complementary resource to the classic model of techno-pedagogical teaching. In this sense, an exhaustive review of the literature was carried out, which focused on four aspects, namely: (a) definition and classification of NS; (b) research findings reported in the literature on the use of SN as an educational resource; (c) contributions of the NS to teaching-learning; and (d) use of SN to support the learning process. We conclude in the first place, that the incorporation of the NS to education is an incontrovertible fact that sooner or later will end up imposing itself as a techno-educational resource in the design and curricular development; secondly, the NS can contribute to the teaching and learning process at the university, becoming a dynamic and complementary factor to the classic model of teacher-centered training; third, the key to success in this educational approach is based on the motivation and technological competence of teachers to promote and implement the appropriate use of said technology to achieve specific learning objectives; and fourth, research in this field is still incipient and focuses mainly on descriptive studies, based mainly on the views of teachers and students on their experiences and perceptions of the use of NS in the educational context.